Electronic structure and ferromagnetism of polycrystalline Zn1-xCoxO (0 <= x <= 0.15) - Deka, Sasanka; Joy, Pattayil Alias (Solid State Communications, 2005)
The electronic structure of polycrystalline ferromagnetic Zn1-x,CoxO (0.05 <= x <= 0.15) and the oxidation state of Co in it, have been investigated. The Co-doped polycrystalline samples are synthesized by a combustion method and are ferromagnetic at room temperature. XPS and optical absorption studies show evidence for Co2+ ions in the tetrahedral symmetry, indicating, substitution of Co2+ in the ZnO lattice. However, powder XRD and electron diffraction data shock the presence of Co metal in the samples. This give evidence to the fact that some Co2+ ion are incorporated in the ZnO lattice which gives changes in the electronic structure whereas ferromagnetism comes from the Co metal impurities present in the samples. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Magnetically ordered materials; Optical properties; Semiconductors

Experimental comparison of the structural, magnetic, electronic, and optical properties of ferromagnetic and paramagnetic polycrystalline Zn1-xCoxO (x=0,0.05,0.1) - Deka, Sasanka; Pasricha, Renu; Joy, Pattayil Alias (Physical Review B, 2006)
Ferromagnetism at room temperature is observed in one case whereas paramagnetism down to 12 K is observed in the second case when polycrystalline Zn1-xCoxO is synthesized under almost identical conditions. Identical x-ray diffraction, optical absorption, and x-ray photoelectron spectroscopy results indicate the incorporation of Co2+ ions in the ZnO lattice in both cases. However, electron diffraction studies show the presence of Co metal impurities in the ferromagnetic samples, indicating that pure Co doped ZnO is not likely to be ferromagnetic.

Enhanced permeability and dielectric constant of NiZn ferrite synthesized in nanocrystalline form by a combustion method - Deka, Sasanka; Joy, Pattayil Alias (Journal of the American Ceramic Society, 2007)
The performance parameters of Ni0.5Zn0.5Fe2O4, synthesized in the nanocrystalline form by an autocombustion method, have been investigated. The sample sintered at 1200 degrees C, with Bi2O3 as additive shows a very high value of initial permeability mu'(i) of > 400 at 1 MHz, with low loss. Similarly, a very high dielectric constant is obtained at lower frequencies. The results show that optimum magnetic and electrical properties can be achieved for the NiZn ferrite nanocrystalline powders synthesized by the present autocombustion method and sintered at a relatively lower temperature of 1200 degrees C when compared with a temperature of 1400 degrees C required for the materials synthesized by the conventional ceramic method.

Enhancement of the phase transformation temperature of gamma-Fe2O3 by Zn2+ doping - Deka, Sasanka; Joy, Pattayil Alias (Journal of Materials Chemistry, 2007)
The phase transformation temperature of gamma-Fe2O3 to alpha-Fe2O3 is increased with Zn2+ doping and enhancement of the transition temperature by similar to 100 degrees C is obtained for doping of >= 15 mol% Zn in nanocrystalline gamma-Fe2O3 synthesized by an autocombustion method.

Exploration of magnetically separable Ag@AgxNiy core/graded-alloy-shell nanostructures - Kumar, Mukesh; Soni, Kiran; Satpati, Biswarup; Gopinath, Chinnakonda S.; Deka, Sasanka (Chemical Communications, 2016)
We report novel bimetallic Ag@AgxNiy core@graded-alloy-shell nanoparticles (CGAS NPs), i.e. single Ag core NPs shelled by an AgxNiy graded alloy and stabilized by the CTAB surfactant employing a novel synthesis method. These Ag@AgxNiy CGAS NPs demonstrated superior catalytic performance in the synthesis of biologically active 3-amino alkylated indoles under green conditions.